(untitled) (Foundations in Clinical Pharmacy Practice, 2025)
Author Dr. Hema Arya, Assistant Professor, Department of Pharmaceutical Chemistry, School of Pharmacy, Sharda University, Greater Noida, Uttar Pradesh, India Abstract Medication therapy management (MTM) provides a systematic framework for optimizing therapeutic outcomes through comprehensive medication review, problem identification, and targeted interventions. Comprehensive medication reviews systematically evaluate all medications including prescription, non-prescription, supplements, and complementary therapies through structured assessment of indication, effectiveness, safety, and adherence. Drug therapy problem identification employs standardized taxonomies categorizing issues including unnecessary therapy, suboptimal dosing, adverse effects, interactions, and adherence barriers requiring resolution. Intervention strategies encompass prescriber collaboration, medication regimen optimization, patient education, care coordination, and documentation with appropriate follow-up planning. Evaluation methodologies assess clinical, economic, and humanistic outcomes through both objective measures and patient-reported experiences using validated instruments and systematic data collection. Quality metrics demonstrate MTM impact through standardized measures addressing medication appropriateness, adherence rates, adverse event reduction, and therapeutic goal achievement. This patient-centered approach improves medication use through personalized interventions addressing specific medication-related needs while reducing healthcare costs, preventing adverse events, and enhancing quality of life through optimized pharmacotherapy. Keywords: Comprehensive Medication Review, Pharmaceutical Care, Drug-Related Problems, Therapeutic Optimization, Outcome Assessment VIEW PDF